An IoT-based Scenario Description Inspection Technique - de Souza, Bruno Pedraça; Motta, Rebeca Campos; Costa, Daniella de O.; Travassos, Guilherme Horta (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2019)
Context: Software inspection is a static and formal verification technique that aims to detect defects in the earlier stage of software development. Both academic and industrial professionals have widely applied software inspections since they reduce by up to 60% the number of defects in artifacts produced in the software development cycle, being a way to assure the quality. Goal: This paper proposes the SCENARIOTCHECK technique, a new approach to supporting the quality of IoT scenarios-based description by performing inspections. Method: We carried out two experimental studies to evaluate the feasibility and observe the use of the technique. Results: In both studies, the technique presented adequate performance and acceptance by the participants when compared with an ad-hoc technique. Besides, the subjects' feedback supported us on improving the SCENARIOTCHECK. Conclusions: SCENARIOTCHECK is a feasible inspection technique that supports the identification of defects in IoT scenarios artifacts.